7x+2=-3+4x+23

Simple and best practice solution for 7x+2=-3+4x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+2=-3+4x+23 equation:


Simplifying
7x + 2 = -3 + 4x + 23

Reorder the terms:
2 + 7x = -3 + 4x + 23

Reorder the terms:
2 + 7x = -3 + 23 + 4x

Combine like terms: -3 + 23 = 20
2 + 7x = 20 + 4x

Solving
2 + 7x = 20 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + 7x + -4x = 20 + 4x + -4x

Combine like terms: 7x + -4x = 3x
2 + 3x = 20 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + 3x = 20 + 0
2 + 3x = 20

Add '-2' to each side of the equation.
2 + -2 + 3x = 20 + -2

Combine like terms: 2 + -2 = 0
0 + 3x = 20 + -2
3x = 20 + -2

Combine like terms: 20 + -2 = 18
3x = 18

Divide each side by '3'.
x = 6

Simplifying
x = 6

See similar equations:

| 11x+2=-24 | | 9v+10=v+9 | | 3.5*2= | | x-19=23 | | 5d+8=53 | | 4x+9-7x=-6 | | 90-x=3/4(180-x)-60 | | 4x+9-7x=-9 | | 0.75=w+2/5 | | (x^2-11)/(2x-1) | | (3/4)x-(7/12)=1 | | 11x-4x=27 | | z/2+1+3/2 | | 3(6x+3)=27 | | 5(2x-4)-(3x+1)=2 | | 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 | | 5+22a=2+10/22 | | 1/4c+2=8 | | 8/4=(6)(0) | | -.2(x+10)-.25(x-4)=x+8 | | 6(X+2)-7=18 | | 0.7t=0.3+0.4t | | 4x-2=9x+1 | | -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= | | -6(-3a-4)= |

Equations solver categories